2019
DOI: 10.1063/1.5058275
|View full text |Cite
|
Sign up to set email alerts
|

The use of strain to tailor electronic thermoelectric transport properties: A first principles study of 2H-phase CuAlO2

Abstract: Using first principles calculations, the use of strain to adjust electronic transport and the resultant thermoelectric (TE) properties is discussed using 2H phase CuAlO2 as a test case. Transparent oxide materials, such as CuAlO2, a p--type transparent conducting oxide (TCO), have recently been studied for high temperature thermoelectric power generators and coolers for waste heat. Given TCO materials with relative ease of fabrication, low cost of materials, and non-toxicity, the ability to tailor them to spec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…In part I of this study [19], it was found that +1% strain in the z direction induced the highest power factors for both n and p type transport in 2H--CuAlO2. A structure with +1% strain in the z direction was simulated for both a crystalline (no grains) as well as for a structure with 3nm grains.…”
Section: B Selected Uni--axial Strainmentioning
confidence: 69%
See 3 more Smart Citations
“…In part I of this study [19], it was found that +1% strain in the z direction induced the highest power factors for both n and p type transport in 2H--CuAlO2. A structure with +1% strain in the z direction was simulated for both a crystalline (no grains) as well as for a structure with 3nm grains.…”
Section: B Selected Uni--axial Strainmentioning
confidence: 69%
“…As we approach the lower limit of the lattice thermal conductivity for complex TE materials the applicability of the field of thermoelectrics remains in question due to the cost and efficiency of working devices. A previous work [19] looked at transparent conducting oxides (TCOs), and specifically 2H--phase CuAlO2, which has gained interest as a promising candidate for high temperature p--type thermoelectric applications [20]- [23] [24], because of its potential use in high temperature applications, due to a large band gap, high thermal stability, oxidation resistance, and low material costs [20], [21], [25]- [34]. Some experimental and theoretical studies [19], [20], [24], [35]- [37], have been done on the thermoelectric (TE) properties of the 2H phase of this material, however none have looked at the thermal conductivity using rigorous first principles simulations.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…[3][4][5] TE properties are complex transport properties, which are hard to be determined both from experimental measurement and theoretical calculation. [6][7][8] To address the current bottleneck of the TE technology, uncover new TE materials with desired performance is urgently needed. Thanks to the everlasting contribution from the TE community, tremendous in-depth research with fruitful research data makes the data-driven approach achievable.…”
Section: Introductionmentioning
confidence: 99%